Association between depressive symptoms and physical exercise in college students: longitudinal mediating effects of social support and psychological resilience - Hou, Yuanyuan; Liu, Xinyi; Li, Zhendong; Huang, Shouzhen; Chen, Wenjuan; Jiang, Yuhao; He, Panpan; Sun, Jingquan; Han, Haijun (Frontiers in Psychology, 2025)
PurposeThis longitudinal study aimed to explore the bidirectional causal relationship between depressive symptoms and physical exercise among college students, with a focus on the mediating roles of social support and psychological resilience.MethodsThe Self-Rating Depression Scale (SDS) was used to assess depression. Physical activity Rating Scale (PARS-3), Perceived Social Support Scale (PSSS), Connor-Davidson Resilience Scale (CD-RISC), A longitudinal study of 1,413 college students was conducted over three months, collecting data at two time points (T1: September 15, 2024; T2: 17 December 2024). In this longitudinal study, 1,350 valid samples were obtained. Primary analyses included independent samples t-test, chi-square test, and Pearson correlation. Amos 28.0 was used to construct the cross-lag model and structural equation model for analysis.Results(1) Depressive symptoms at T1 negatively predicted physical activity at T2 (β = −0.07, p < 0.05). Physical exercise at T1 negatively predicted depressive symptoms at T2 (β = −0.08, p < 0.05), and depressive symptoms and physical exercise could predict each other. (2) Social support at T2 played a delayed mediating role in depressive symptoms at T1 and physical exercise at T2 (β = −0.02, [−0.049, −0.006], p < 0.01). (3) Resilience at T2 played a delayed mediating role in depressive symptoms at T1 and physical exercise at T2 (β = −0.03, [−0.049, −0.002], p < 0.01). (4) Social support and resilience at T2 played a delayed chain mediating role in depressive symptoms and physical exercise at T1 (β = −0.01, [−0.024, −0.005], p < 0.01).ConclusionThis study highlights the importance of social support and resilience in promoting physical exercise and alleviating depressive symptoms in college students, as well as the interrelationship between depressive symptoms and physical exercise. The results showed that depressive symptoms not only directly affected physical exercise of college students, but also indirectly affected physical exercise of college students through the independent mediating effect of social support and psychological resilience and the chain mediating effect of social support-psychological resilience. In practice, we should improve the social support system and improve the psychological resilience of college students, which can effectively alleviate the depressive symptoms of college students and enhance physical exercise.